Healthy Eating: Food Storage Guide - Linda B. Bobroff; Jennifer Hillan (EDIS, 2013)
If you don’t shop for groceries often, you may want to buy food that will last until your next trip to the store. The following storage guidelines for perishable foods will help you decide how much food to buy when you visit the grocery. Keep in mind that safe storage times depend on the condition of the food when you purchase it and your refrigerator temperature and humidity. Check foods often for any signs of spoilage. This 2-page fact sheet was written by Linda B. Bobroff and Jennifer Hillan and published by the UF Department of Family Youth and Community Sciences, October 2013.